2020
DOI: 10.32098/mltj.01.2020.22
|View full text |Cite
|
Sign up to set email alerts
|

Defensive Antibacterial Coating (DAC®) for prevention of infection in ACL reconstruction: a feasibility study

Abstract: Defensive Antibacterial Coating (DAC) is a hydrogel, Conformité Européene (CE)-marked medical device, intended to be used as a disposable, quickly bioresorbable antibacterial coating for implants. The present feasibility study investigated the application of DAC on the grafts, in addition to IV prophylaxis, during anterior cruciate ligament (ACL) reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…There is a renewed interest in the prevention of infection in ligament reconstruction surgery. It is possible that devices developed for intra-articular ligament reconstruction procedures may well be used in MPFL reconstruction, especially when employing allografts [ 2 ]. Surgeons must be aware of the storage processes, sterilization methods, and standards of the tissue bank they use.…”
Section: Discussionmentioning
confidence: 99%
“…There is a renewed interest in the prevention of infection in ligament reconstruction surgery. It is possible that devices developed for intra-articular ligament reconstruction procedures may well be used in MPFL reconstruction, especially when employing allografts [ 2 ]. Surgeons must be aware of the storage processes, sterilization methods, and standards of the tissue bank they use.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the clinical applications, our injectable systems could adjust paste to the defect surfaces and shape in situ for dental and craniofacial reconstructions with the minimal access. Also, the use of defensive antibacterial coating (DAC) has been reported to be easily applied in on the grafts, during anterior cruciate ligament reconstruction [ 29 ]. Previous studies reported that CPC, even containing pyrogens and chopped fibers, could be rendered injectable via a 10-gauge needle [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Covalently immobilized AG coatings have shown good antifouling properties with significant reduction in bacterial and protein adhesion as well as inhibition of biofilm formation compared to the uncoated surfaces. Hyaluronic acid (HA) is an anionic glycosaminoglycan (GAG) polysaccharide that attracts water molecules and forms viscous hydrogels . An antifouling and fast-resorbable hydrogel coating based on graft copolymers of HA with poly- d , l -lactic acid (PLA), called Defensive Antibacterial Coating (DAC), has been recently developed for orthopedic and dental applications . Heparin (HEP) is another GAG, whose negatively charged sulfate and sulfamate groups contribute to its anticoagulant and antithrombotic properties in addition to inhibiting bacterial adhesion and biofilm formation. , However, the antibacterial activity of HEP is still debatable since free HEP has been shown to stimulate Staphylococcus aureus ( S. aureus , a major human bacterial pathogen) biofilm formation, and under some circumstances, HEP coatings may even promote S. aureus attachment. …”
Section: General Antifouling and Bactericidal Strategiesmentioning
confidence: 99%
“…54 An antifouling and fast-resorbable hydrogel coating based on graft copolymers of HA with poly-D,L-lactic acid (PLA), called Defensive Antibacterial Coating (DAC), has been recently developed for orthopedic and dental applications. 55 Heparin (HEP) is another GAG, whose negatively charged sulfate and sulfamate groups contribute to its anticoagulant and antithrombotic properties in addition to inhibiting bacterial adhesion and biofilm formation. 56,57 However, the antibacterial activity of HEP is still debatable since free HEP has been shown to stimulate Staphylococcus aureus (S. aureus, a major human bacterial pathogen) biofilm formation, and under some circumstances, HEP coatings may even promote S. aureus attachment.…”
Section: General Antifouling and Bactericidalmentioning
confidence: 99%